The Interconnection between Brahman and Atman: An Explication of Adi Shankara’s Writings - Gordon, Brandon Lee (The international journal of religion and spirituality in society, 2013)
The Vedic texts are sacred to many Hindus. Adi Shankara was a 9th century Hindu mystic and commentator of the Vedic texts that explicate the philosophical view of Advaita Vedanta. While there are some problems still not solved in Shankara’s meaning at this time, there is a consensus as to his intent in his writings about the Oneness of Brahman and Atman and how one is to come to know this connection. The commentators that I use to shed light on Shankara’s meaning are N. K. Devaraja, Eric Lott, and Arvid Sharma. According to Shankara, whose position I sympathize with, we come to know Atman, Brahman and the Oneness, ultimately, though not exclusively, through direct experience. Primarily, the purpose of this essay is to explicate and qualify the truth of Shankara’s position. Secondarily and more specifically, I argue that either Shankara exaggerates the delusional nature of the external world or that there are a few mistranslations concerning the external world. I attempt to fulfill this purpose by first answering the question of how one is supposed to come to know Atman, Brahman, and the connection between the two. Next, I will answer the question of what we can know about Atman, Brahman, and the Oneness. These questions will be answered by analyzing Shankara’s text and secondary sources. I will also provide a few personal illustrations for clarification that could be interpreted as direct experiences of Oneness that Shankara discusses.